THE AWAKENING OF THE GIANT: THE CHINESE CIVILIZATION-STATE AND ITS GLOBAL AMBITION - Ilik, Goran (Horizons - International Scientific Journal, 2020)
This paper presents the basic premises of China as an emerging global actor with all its specificities of civilization-state. The Chinese civilization has an essential and complex body. It is this feeling of civilizational grandeur that generates a conviction in Chinese greatness. Special emphasis is given to the new global strategy of China, as a doctrine of President Xi Jinping. This new strategy is especially highlighted through the “Belt and Road Initiative” (BRI) as the biggest project of the century and its 17+1 framework. The direct investment of China in countries around the world, appear as latent and hegemonic instruments for expansion of its political influence. Both, the BRI and the 17+1 framework represent triggers for achieving the Chinese global ambition.